Approaching Biomarkers of Membranous Nephropathy from a Murine Model to Human Disease. (30th December 2010) - Wu, Chia-Chao; Chen, Jin-Shuen; Huang, Ching-Feng; Chen, Chun-Chi; Lu, Kuo-Chen; Chu, Pauling; Sytwu, Huey-Kang; Lin, Yuh-Feng
Abstract : Background . Membranous glomerulonephropathy (MN) is the most prevalent cause of nephrotic syndrome in adult humans. However, the specific biomarkers of MN have not been fully elucidated. We examined the alterations in gene expression associated with the development of MN. Methods . Murine MN was induced by cationic bovine serum albumin (cBSA). After full-blown MN, cDNA microarray analysis was performed to identify gene expression changes, and highly expressed genes were evaluated as markers both in mice and human kidney samples. Results . MN mice revealed clinical proteinuria and the characteristic diffuse thickening of the glomerular basement membrane. There were 175 genes with significantly different expressions in the MN kidneys compared with the normal kidneys. Four genes, metallothionein-1 (Mt1), cathepsin D (CtsD), lymphocyte 6 antigen complex (Ly6), and laminin receptor-1 (Lamr1), were chosen and quantified. Mt1 was detected mainly in tubules, Lamr1 was highly expressed in glomeruli, and CtsD was detected both in tubules and glomeruli. The high expressions of Lamr1 and CtsD were also confirmed in human kidney biopsies. Conclusion . The murine MN model resembled the clinical and pathological features of human MN and may provide a tool for investigating MN. Applying cDNA microarray analysis may help to identify biomarkers for human MN.